The Public Value of e-Government at The Village Level - Yayan Muhammad Royani; Dian Herdiana; Idah Wahidah (Department of Public Administration, 2022)
The villages as a local government directly serve the public should always provide good public services. On this basis, this article analyzes how the implementation of e-Government by village governments can contribute positively to village`s governance and public service seen from a public values perspective. The research method used in this research is the descriptive research method with a qualitative approach. Sources of data come from secondary sources from books, journal articles and other relevant documents. The results of the analysis revealed that there are at least 3 (three) public values from the adoption of e-Government at the village level, namely: First, the commitment of the village government to provide technology-based public services would create good public services. Second, the implementation of e-Government ensures the public's right to participate in government administration in which the adoption of technology and information provides rights for open and collaborative governance. Third, the implementation of e-Government encourages the acceleration of a digital society which would contribute positively to village development and create public welfare.